Self Efficacy: Performance Accomplishment dan Perilaku Merokok Remaja - Haryati, Wiwin; Abdullah, Asnawi; Bakhtiar, Bakhtiar (Jurnal Riset Hesti Medan, 2020)
Smoking behavior among teenagers has been increasing worldwide, triggering youth morbidity and mortality rates associated with smoking illnesses. Performance accomplishment, source of self-efficacy, has a significant influence on the high proportion of teenage smoking behavior. The purpose of this study was to assess the relationship between performance accomplishment and teenage smoking behaviors. The study was conducted on April 16 – 23, 2015 in Aceh Province, Indonesia. Data were collected by disseminating a Likert scale questionnaire, consisting of general perceived self-efficacy, including performance accomplishment. The population of this study were 4,856 students, with a total sample of 368 students from 13 senior high schools. The study employed an analytic observational research design with the stratified proportional random sampling technique. Bivariate analysis by Chi-square test was applied to examine the data, processed by using SPSS version 20.0. The results indicated that there were significant relationships between self-efficacy and teenage smoking behavior (p=0.0001) and between performance accomplishment and teenage smoking behavior (p=0.0001). This study concluded that performance accomplishment has been strongly associated with the smoking behavior among young adults.